PENERAPAN LANGKAH-LANGKAH POLYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM MENYELESAIKAN SOAL CERITA HIMPUNAN DI KELAS VII SMP NASIONAL WANI - Nurhayati, Nurhayati (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
ABSTRCT: The purpose of this research is to obtain a description of the application of Polya steps that can improve student learning outcomes in solving word problems in the operation of two sets in class VII SMP Nasional Wani. This type of research is classroom action research with research design refers to the model of Kemmis and Mc. Taggart. The results show that the learning using Polya steps to improve student learning outcomes in solving word problems set in class VII SMP National Wani, including guiding students based on four steps Polya, namely: (1) Understanding the problem, (2) Make a plan, (3) Implement the Plan, (4) Looking back or recheck.